2009
DOI: 10.3892/mmr_00000084
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial depolarization and apoptosis associated with sustained activation of c-jun-N-terminal kinasein the human multiple myeloma cell line U266 induced by 2-aminophenoxazine-3-one

Abstract: Abstract.We investigated the involvement of c-jun-N-terminal kinase (JNK) in mitochondrial depolarization and apoptosis in a human multiple myeloma cell line, U266, treated with 2-aminophenoxazine (Phx-3). It was found that, with Phx-3 administration to U266 cells, JNK was phosphorylated 2 and 7.5-fold at 6 and 24 h, respectively, compared to the Phx-3-free control. This increasing activation of JNK in U266 cells with Phx-3 correlated with cellular disorders, such as mitochondrial depolarization and cellular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In gastric and colon cancer cells, treatment with Phx-3 significantly depolarizes mitochondria, followed by apoptotic cell death of these cancer cells [8,16]. This result is consistent with recent reports [6,8] that Phx-3 depolarizes mitochondria in a variety of cancer cell lines originating from different organs. Therefore, Phx-3 may exert strong anticancer activity on gastric and colon cancers via depolarization of mitochondria in these cells.…”
Section: Direct Anticancer Activity Of Phx-3 On Gastric and Colon supporting
confidence: 90%
“…In gastric and colon cancer cells, treatment with Phx-3 significantly depolarizes mitochondria, followed by apoptotic cell death of these cancer cells [8,16]. This result is consistent with recent reports [6,8] that Phx-3 depolarizes mitochondria in a variety of cancer cell lines originating from different organs. Therefore, Phx-3 may exert strong anticancer activity on gastric and colon cancers via depolarization of mitochondria in these cells.…”
Section: Direct Anticancer Activity Of Phx-3 On Gastric and Colon supporting
confidence: 90%
“…Mitochondrial dysfunction is closely associated with apoptosis ( 22 ); therefore, the levels of apoptosis were determined in the present study. The results of flow cytometry demonstrated that the rate of apoptosis was lower in the DOX + siCUE group compared with in the DOX group ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate that Phx-3 has a strong ability to depolarize the mitochondria in cancer cells, consistent with recent reports that Phx-3 is involved in depolarization of the mitochondria in multiple myeloma cell line U266 cells. 50,51) Currently, it is unclear why Phx-3 had less effect on the depolarization of mitochondria in KLM-1, MIA PaCa-2 cells and Y-79 cells.…”
Section: Discussionmentioning
confidence: 99%